Changes in Global Production Patterns and Impacts on Enterprises and Employment. Issue 2 (27th April 2017) - Corley‐Coulibaly, Marva; Kizu, Takaaki; Kühn, Stefan; Peels, Raphael; Viegelahn, Christian
Abstract : This chapter examines global trends in the internationalization of production and presents new estimates of the number of jobs linked to global supply chains, providing both aggregate figures and figures by sector and sex. The chapter finds that 453 million jobs were related to global supply chains in 2013 in the 40 countries covered by the estimates, an increase from 296 million jobs in 1995. The chapter also discusses results of a sector‐level analysis in which empirical relationships between a sector's participation in global supply chains and selected indicators are identified from both the lead and the supplier firm perspective. Results suggest that, at least in developed economies, there is a positive impact of global supply chain participation on productivity, while no such impact on wages is found. The chapter concludes by exploring the policy options that are available to ensure that economic benefits of global supply chain participation translate into benefits for workers.